2018
DOI: 10.1148/rg.2018180080
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis: A Sonographic Diagnosis

Abstract: Adenomyosis is a common benign uterine condition and a frequent cause of pelvic pain in premenopausal women. Transvaginal US is now considered the primary imaging modality for the diagnosis of adenomyosis, and thus radiologists should be familiar with its sonographic appearance. US findings can be divided into three categories, which parallel the histology of adenomyosis: (a) ectopic endometrial glands and stroma, (b) muscular hyperplasia/hypertrophy, and (c) increased vascularity. Ectopic endometrial glands m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 29 publications
0
78
0
7
Order By: Relevance
“…Despite considerable public health burden, associated costs of care, and impacts on the lives of many women, reliable population-based incidence estimates of adenomyosis do not exist 3 and studies on prevalence vary widely. 9 To address this gap, we conducted a retrospective cohort study using electronic health records (EHR) to estimate the incidence of symptomatic adenomyosis over a 10-year period (2006e2015) and symptomatic adenomyosis prevalence (2015) in a U.S. population. Secondary aims were to estimate incidence rates by age and by race/ ethnicity, to evaluate trends, and to describe symptoms and treatment practice patterns.…”
mentioning
confidence: 99%
“…Despite considerable public health burden, associated costs of care, and impacts on the lives of many women, reliable population-based incidence estimates of adenomyosis do not exist 3 and studies on prevalence vary widely. 9 To address this gap, we conducted a retrospective cohort study using electronic health records (EHR) to estimate the incidence of symptomatic adenomyosis over a 10-year period (2006e2015) and symptomatic adenomyosis prevalence (2015) in a U.S. population. Secondary aims were to estimate incidence rates by age and by race/ ethnicity, to evaluate trends, and to describe symptoms and treatment practice patterns.…”
mentioning
confidence: 99%
“…19 Definitive diagnosis is by histologic examination at hysterectomy; however, specific TVUS and magnetic resonance imaging (MRI) criteria help establish the diagnosis. 20,21 Transvaginal ultrasound may include echogenic striations, myometrial cysts, globular uterus configuration or asymmetrical thickening of the myometrium, and heterogeneity of the myometrium leading to poor definition of the endometrialmyometrial interface (sensitivity, 89%; specificity, 89%). 20 Given that adenomyosis increases uterine vascularity, a pattern of penetrating vessels can be seen at color Doppler ultrasound.…”
Section: Polypsmentioning
confidence: 99%
“…20,21 Transvaginal ultrasound may include echogenic striations, myometrial cysts, globular uterus configuration or asymmetrical thickening of the myometrium, and heterogeneity of the myometrium leading to poor definition of the endometrialmyometrial interface (sensitivity, 89%; specificity, 89%). 20 Given that adenomyosis increases uterine vascularity, a pattern of penetrating vessels can be seen at color Doppler ultrasound. 20 T2-weight MRI findings may show diffuse or focal endometrialmyometrial junctional zone widening of 12 mm or more, islands of heterotopic endometrial tissue, cystic dilation of heterotopic glands, and punctate hyperintense foci of hemorrhage (sensitivity, 86%; specificity, 86%) 21 (Figure 2).…”
Section: Polypsmentioning
confidence: 99%
“…At TVUS, ectopic endometrial glands appear as echogenic nodules, striations radiating from the endometrium into the myometrium or myometrial cysts, whereas muscular hyperplasia and hypertrophy are seen as focal or diffuse myometrial thickening or asymmetric globular uterine enlargement. MRI is particularly useful in detecting the thickening, hyperplasia, or disruption of the uterine junctional zone (JZ) located between the endometrium and the internal myometrium [8,9]. It has been shown that the accuracies of two-dimensional TVUS, MRI, and histology are comparable in diagnosing adenomyosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic imaging has improved the understanding of adenomyosis in women of all ages and has allowed to investigate the relationship between adenomyosis and infertility [9].…”
Section: Introductionmentioning
confidence: 99%